2020
DOI: 10.1159/000510723
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Accuracy of Thymus and Activation-Regulated Chemokine to Discriminate Food Protein-Induced Enterocolitis Syndrome from Infectious Gastroenteritis

Abstract: Background: Post-emetic elevation in thymus and activation-regulated chemokine (TARC) levels has been reported in patients with food protein-induced enterocolitis syndrome (FPIES); however, no studies have investigated differences in TARC levels between FPIES and other diseases. Objectives: We evaluated the clinical usefulness of TARC measurement in differentiating between FPIES and infectious gastroenteritis. Methods: This study included 8 patients with solid-food FPIES (FPIES group; hen’s egg [n = 6], rice [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…TARC is a Th2 biomarker used for the diagnosis of atopic dermatitis and in the evaluation of its severity [8]. We recently reported that serum TARC levels were elevated after vomiting in patients with solid food FPIES and that they were correlated with symptomatic severity [5,6]. In this study, we hypothesized that post-emetic TARC levels in egg yolk FPIES could predict the result of an OFC performed with the same amount of egg yolk after a given duration, and evaluated the management of FPIES based on an annual OFC.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…TARC is a Th2 biomarker used for the diagnosis of atopic dermatitis and in the evaluation of its severity [8]. We recently reported that serum TARC levels were elevated after vomiting in patients with solid food FPIES and that they were correlated with symptomatic severity [5,6]. In this study, we hypothesized that post-emetic TARC levels in egg yolk FPIES could predict the result of an OFC performed with the same amount of egg yolk after a given duration, and evaluated the management of FPIES based on an annual OFC.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We reported that patients with solid FPIES exhibited higher serum thymus and activation-regulated chemokine (TARC; a Th2 chemokine) levels after vomiting compared to other diseases. Moreover, the post-emetic TARC levels were correlated with symptom severity in FPIES [5,6]. This study evaluated the post-emetic TARC levels, clinical symptoms, and post-index event results of the egg yolk OFC and retrospectively investigated predictive factors for the subsequent OFC result.…”
Section: Introductionmentioning
confidence: 99%
“…46 High levels of the chemokine are seen in patients with food-induced anaphylaxis, 73 gastrointestinal food allergies 74 and childhood allergy development, 75 with elevated CCL17 serum levels reported to be a potential diagnostic biomarker for food protein-induced enterocolitis syndrome, which is a non-immunoglobulin E-mediated gut allergic response. 76 Its tear levels have even been suggested to be a diagnostic biomarker for acute and chronic allergic conjunctival disorders, 77 and atopic and vernal keratoconjunctivitis. 78 These studies again highlight the potential for CCL17 to serve at least as a diagnostic biomarker for numerous diseases.…”
Section: Additional Autoimmune/inflammatory Diseasesmentioning
confidence: 99%
“…53 Makita et al reported that blood thymus and activation-regulated chemokine (TARC) levels were higher in FPIES patients visiting the emergency department or conducting OFC than in gastroenteritis or sepsis patients, and that high TARC levels persisted for 6-24 h after the onset of symptoms. 54 They also reported that blood TARC levels at the onset of symptoms in FPIES patients were higher than those in patients with IgE-mediated food allergy at the onset of symptoms, and measuring blood TARC levels in patients presenting to the emergency department with vomiting symptoms may be useful in distinguishing emesis caused by FPIES from vomiting caused by gastroenteritis and IgE-mediated food allergy. 55 However, evaluation of blood TARC level should be conducted with care in patients with eczema because they already have elevated blood TARC levels.…”
Section: Allergen Lymphocyte Stimulation Test (Alst)mentioning
confidence: 99%